The Effect of Applying Summarizing Strategy toward Students’ Reading Comprehension in Exposition Text: an Experimental Research at Second Grade Students of MAN 2 Padang - Amelia Hamida; Zainuddin Amir; Fitrawati Fitrawati (Journal of English Language Teaching, 2012)
Abstract This study aimed to see the effect of using summarizing strategy toward students’ reading comprehension in reading. This study was an experimental research. The population was the students of eleventh grade of MAN 2 Padang registered for the 2011/2012 academic year. Sample used by using cluster random sampling which was gotten XI IPA 1 as experimental class and XI IPA 2 as control class. The test was done twice: pretest and posttest. The instrument was reading comprehension test. The data was the students’ score of reading comprehension test and was analyzed statistically by using t-test. Based on the counting, it can be concluded that the using of summarizing strategy in reading can give the good effect of students’ reading comprehension. Abstrak Penelitian ini bertujuan untuk melihat dampak penggunaan strategi meringkas terhadap pemahaman siswa dalam membaca. Jenis penelitian ini adalah penelitian eksperimen. Populasi penelitian ini siswa kelas XI MAN 2 Padang tahun ajaran 2011-2012. Sampelnya menggunakan teknik cluster random sampling dan terpilihlah kelas XI IPA 1 sebagai kelas eksperimen dan XI IPA 2 sebagai kelas control dengan. Tes dilakukan dua kali: pretest dan posttest. Instrumentnya berupa soal pemahaman membaca. Data berupa nilai tes pemahaman membaca oleh kedua kelompok sampel dianalisis secara statistik dengan menggunakan rumus t-test. Berdasarkan hasil hitungan ini, disimpulkan bahwa penggunaan strategi meringkas dalam pemelajaran membaca dapat memberikan pengaruh yang lebih baik terhadap pemahaman siswa dalam membaca.